Repair of traumatic degloving injuries involving fingers using random abdominal flap - ملحم, فراس (Latakia University Journal -Medical Sciences Series, 2022)
Degloving injury of the fingers continues to be one of the most chalenging and debilitating injuries. This injury can leave large skin defects overlying important structural repairs to tendon, bone and nerve. This injury must be quickly treated. An operation of choice is to be found. The finger degloving injuries could be successfully resurfaced with abdominal flaps.This method offers immediate total wound coverage in multiple-finger degloving injuries. This study aims to evaluate the outcome of the reconstruction of the degloving injury involving multiple fingers using random abdominal flap. The flap was designated to wrap the entire circumference of the fingers sustaining degloving injury. Good coverage of the soft tissue defects with good appearance was achieved. The donor defect could be easily covered with split-thickness skin graft. A retrospective study of our outcome of 10 performed finger degloving injuries reconstruction. All these patients were operated using the proposed surgical technique between 2017 and 2020 in Tishreen University Hospital in Lattakia, Syria. Patients ranged from 25 to 45 years (mean 35 years). six patients were males. The reconstruction was performed immediately after the injury. Results of surgery were graded as excellent to good depending upon the outcome of the flap. Minor complications were noted but none required a separate operative procedure. We have found this procedure to be reliable, technically easy, and esthetically acceptable.